TOURISM AND ITS TYPES - Khasanova Nargiza Atamovna; Olimboev Solijon Komiljon; Eminjonov Dilmurod Abdusalam (Web of Journals Publishing, 2024)
This article examined the concept of tourism and its types.
Keywords: tourism, trade, resort, globalization.